Avaliação subjetiva do desempenho de soluções de isolamento sonoro ao ruído de impacto - Panosso, Andriele da Silva (2015)
The aim of this study was to evaluate the subjective acoustic performance of soundproofing solutions for impact noise commonly used in Brazil. Therefore it was developed a subjective evaluation protocol that has gone through several stages: adaptation of the data acquisition environment, obtaining sound signals and objective evaluation, preparation of the experimental protocol, pilot testing, final subjective evaluation and analysis of subjective data and correlation with objective data. Two types of floors were used, thirteen resilient materials currently found in the market and two impact sound sources. According to the objective evaluation, the performances of the samples tested with the standard tapping machine had several different results, two materials were classified with superior performance (according to NBR 15575:2013) and only one material was rated with minimum performance. The others presented intermediate performance in a wide range of results. The performance of the samples tested with the impact tire/ball were more similar to each other. The performance of the samples tested with the impact tire/ball were more similar to each other and a performance rating was not carried out because there is no specific legislation to do so. The samples of the subjective evaluation were selected based on a similarity criteria that took into account similarities in the spectra of different floor/source/resilient materials combinations. 56 samples were evaluated objectively and 49 samples subjectively. The analysis of the subjective evaluation results demonstrated through more detailed data, that the perception of the jury is more accurate when the source of impact assessed is the standardized tapping machine. The samples tested with the impact tire/ball were more similar to each other and results of performance in two different cases was demonstrated negative. The results of correlation and linear regression between objective and subjective data showed that for samples using standardized tapping machine, the objective parameters are strongly correlated with subjective (annoyance and loudness), regardless of the type of flooring used. It was also demonstrated that the objectives parameters obtained with measurements made with porcelain floor and the impact tire/ball is strongly correlated with the subjective parameters (annoyance and loudness). The objective parameters measured with laminate flooring samples and impact tire/ball showed moderate to little or no correlation with annoyance. The correlation between loudness sensation and objective parameters resulted moderated to strong. As a result of this work an individual evaluation report was created for each of the tested resilient materials, with the objective and subjective data, in which the performance according to different criteria addressed can be verified. It was also evident from the analysis of correlation and linear regression that objective parameters are good descriptors for annoyance and loudness.